COMPARISON OF THE SUSTAINABLE BUSINESS GROWTH METHODS IN SMEs ALGERIA AND EU - Tayebi Abdallah,; Benba Djelloul,; Seddiki Ahmed, (International Journal of Innovative Technologies in Social Science, 2025)
The purpose of the proposed study is to elaborate the comprehensive framework to sustain growth in the context of small and medium-sized enterprises (SMEs) through the analysis of the prospective drivers of sustainability as identified in the realms of economics, organizational behavior, and environment. By making a comparative study of Algeria and the European Union (EU), the study outlines the major differences between the two scenarios and attempts to make lessons out of the achievements of European activities. SMEs are challenged with various challenges, such as the lack of finance and reinforced digital infrastructure, lack of institutional support, and complicated regulatory environments that are undermining their enterprising opportunities and potential suicides. Conversely, the member states within the EU have set in common systems that lead to innovations, protecting the environment and modernizing technologies. The study has an analytical framework based on the discussions of the role of the economy, organizational forces and community involvement/action in facilitating sustainable development and has been able to give a conclusive analysis of the level of Algeria as compared with the EU. It determines the primary challenges facing Algerian SMEs - especially financial and poor digital resources and suggests that by implementing aspects of the effective policies of the EU, it is possible to promote modernization and sustainability of the sector of the SMEs in Algeria.